2015
DOI: 10.1016/j.physleta.2015.02.034
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure of a graphene superlattice with a modulated Fermi velocity

Abstract: The electronic structure of a graphene superlattice composed by two periodic regions with different Fermi velocity, energy gap and electrostatic potential is investigated by using an effective Dirac-like Hamiltonian. It must be expected that the change of the Fermi velocity in one region of the graphene superlattice is equivalent to changing the width of this region keeping the Fermi velocity unchanged, provided that the time taken to charge carriers cross the region is the same. However, it is shown here that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…In the contact points, where the band structures are intersected, the gradient of dispersion relation (39) must be equal zero [24]. This implies that the contact point (k xc , k yc , ε c ) has to verify f (k xc , k yc , ε c ) = 0, ∇f (k xc , k yc , ε c ) = 0. where the involved parameter is…”
Section: Appendixmentioning
confidence: 99%
“…In the contact points, where the band structures are intersected, the gradient of dispersion relation (39) must be equal zero [24]. This implies that the contact point (k xc , k yc , ε c ) has to verify f (k xc , k yc , ε c ) = 0, ∇f (k xc , k yc , ε c ) = 0. where the involved parameter is…”
Section: Appendixmentioning
confidence: 99%
“…At the Dirac point (k Dx , k Dy , ε D ), the band structures are intersected. Then the gradient of dispersion relation must be equal zero [17], namely…”
Section: Model and Methodsmentioning
confidence: 99%
“…In the last years, various studies have revealed that the electronic and transport properties of graphene can be controlled by a Fermi velocity engineering [43,44]. For instance, it was obtained that a Fermi velocity modulation in graphene can control the energy gap [45] and also induce an indirect energy gap in monolayer [46] and bilayer [47] graphene.…”
Section: Introductionmentioning
confidence: 99%